Novas Neolignanas de Krameria tomentosa A. St.-Hil. (Krameriaceae) - Madeiro, Sara Alves Lucena (2012)
The genus Krameria is the only member of Krameriaceae family, comprising 18 herbaceous or shrub species. Among these, there is Krameria tomentosa A. St.-Hil., popularly known ratanha de Nova Granada , carrapicho de cavalo or ratanha de salvanille . In this work, the isolation and structural elucidation of neolignans from the roots of K. tomentosa is described. The dried and pulverized plant material was subjected to extraction, partition and chromatography processes for isolation of chemical constituents. The chemical structures are determined by spectroscopic methods such as Infrared, 1H and 13C Nuclear Magnetic Resonance, Mass Spectrometry and comparison with literature. The hexane and dichloromethane extracts yielded five neolignans: eupomatenoid 6 and 2-(2 ,4 -dihydroxyphenyl-5-(E)-propenylbenzofuran, described for the first time in the especies, dihydrocarinatidin, described for the first time in the family, 1,1 -(E)-propenyl-4-methoxy-3,4 -oxyneolignan and 5-acid-2-(2 -hydroxy-4 ,6 -dimethoxyphenyl)-benzofuranic, described for the first time in the literature, and trivially named ottomentosa e sobralin, respectively. Thus, the obtained results contributed with chemotaxonomic knowledge of Krameriaceae family, in particular the species Krameria tomentosa.